2016
DOI: 10.2217/whe.15.81
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Heavy Menstrual Bleeding

Abstract: Heavy menstrual bleeding (HMB) is a common gynecological complaint with multiple etiologies and diverse pathophysiological origins. This review discusses HMB with reference to the recently proposed PALM-COEIN classification system for abnormal uterine bleeding, initially describing the endometrial events in normal menstruation followed by discussion of the perturbations of normal endometrial shedding that can result in HMB. Our present understanding of the mechanisms of menstrual bleeding as well as many of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 84 publications
(162 reference statements)
1
60
3
1
Order By: Relevance
“…Irregular bleeding arises from endometrial hemostasis and structural impairments due to inflammation and oxygen stress. The aberrant activities of proteins that regulate angiogenesis appear to contribute to breakthrough bleeding (Lockwood, ; Kayisli et al, ; Hapangama and Bulmer, ), although the exact molecular mechanism is not yet fully elucidated. The use of progesterone subcutaneous implants in mice and guinea pigs represent a convenient model for the investigation of the mechanisms underlying irregular endometrial tissue breakdown or abnormal bleeding in women using LTPOCs (Morison et al, ; Alvarez Gonzalez et al, ; Krikun et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Irregular bleeding arises from endometrial hemostasis and structural impairments due to inflammation and oxygen stress. The aberrant activities of proteins that regulate angiogenesis appear to contribute to breakthrough bleeding (Lockwood, ; Kayisli et al, ; Hapangama and Bulmer, ), although the exact molecular mechanism is not yet fully elucidated. The use of progesterone subcutaneous implants in mice and guinea pigs represent a convenient model for the investigation of the mechanisms underlying irregular endometrial tissue breakdown or abnormal bleeding in women using LTPOCs (Morison et al, ; Alvarez Gonzalez et al, ; Krikun et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…There all cause of menorrhagia is unknown although recent studies have reported fibrinolysis and imbalance of prostaglandins as the cause of excessive uterine bleeding 3,4 . Routine treatment so of menorrhagia include oral contraceptives with estrogen or progesterone alone, gonadotropinreleasing hormone agonists, anti-fibrinolytics, nonsteroidalanti-inflammatory drugs such as mefenamic acid and desmopressin 5 .…”
Section: Ijpsr (2018) Volume 9 Issue 4 (Research Article)mentioning
confidence: 99%
“…HMB is a common medical reason for referral to hospitals. Clinically it is defined as more than 80 mL blood loss per cycle and/or a menstrual bleeding period of longer than 7 days . HMB is a complaint with multiple aetiologies and diverse pathophysiology that is incompletely understood .…”
Section: Introductionmentioning
confidence: 99%
“…Clinically it is defined as more than 80 mL blood loss per cycle and/or a menstrual bleeding period of longer than 7 days. 5 HMB is a complaint with multiple aetiologies and diverse pathophysiology that is incompletely understood. 6 In 40% of the women, a clear pathophysiological cause can be diagnosed, including hormonal imbalances, dysfunctions in the ovaries and polyps, fibroids, or adenomyosis in the uterus.…”
mentioning
confidence: 99%
See 1 more Smart Citation